2018
DOI: 10.1084/jem.20171810
|View full text |Cite
|
Sign up to set email alerts
|

BCAP links IL-1R to the PI3K–mTOR pathway and regulates pathogenic Th17 cell differentiation

Abstract: The toll-like receptor (TLR) and interleukin (IL)-1 family of receptors share several signaling components, including the most upstream adapter, MyD88. We previously reported the discovery of B cell adapter for phosphoinositide 3-kinase (BCAP) as a novel toll-IL-1 receptor homology domain-containing adapter that regulates inflammatory responses downstream of TLR signaling. Here we find that BCAP plays a critical role downstream of both IL-1 and IL-18 receptors to regulate T helper (Th) 17 and Th1 cell differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 52 publications
2
52
0
Order By: Relevance
“…Inhibitors of PI3K reduced tumor burden through limiting recruitment of immunosuppressive components including MDSCs and Treg cells in tumors (11,37,38). In this study, we revealed that Pik3ip1, a critical regulator of PI3K, serves as an essential rheostat for T-cell-mediated immunity, which sets the threshold for T-cell responses under homeostatic conditions and neoantigen exposure, especially tumor antigen stimulation.…”
Section: Discussionmentioning
confidence: 73%
“…Inhibitors of PI3K reduced tumor burden through limiting recruitment of immunosuppressive components including MDSCs and Treg cells in tumors (11,37,38). In this study, we revealed that Pik3ip1, a critical regulator of PI3K, serves as an essential rheostat for T-cell-mediated immunity, which sets the threshold for T-cell responses under homeostatic conditions and neoantigen exposure, especially tumor antigen stimulation.…”
Section: Discussionmentioning
confidence: 73%
“…49 Moreover, IL-1R signaling induced PI3K/AKT phosphorylation and mTOR activation to promote differentiation of pathogenic T H 17 cells. 50 Our data indicate that inhibition of PI3K/AKT or amino acid depletion abrogated mTOR activation induced by IL-23 and IL-1b in gd T cells. Importantly, PI3K/AKT signaling is important for expansion of IL-17-secreting gd T cells.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, these patients show increased eosinophil counts in their BALF. It has recently been proposed that signaling through the IL-1R in CD4 + T cells drives the induction of pathogenic Th17 cells involved in the development of autoimmunity (43). Whether CLCs, which are a hallmark of eosinophilic diseases, are present in the BALF of Th2/Th17-predominant asthma patients, and whether their recognition by alveolar macrophages are the cause of the increased levels of IL-1b, is a matter of further research.…”
Section: Discussionmentioning
confidence: 99%
“…Protein-enriched samples during the process of CLC generation were mixed with NuPAGE LDS Sample Buffer (43) and with NuPAGE Sample Reducing Agent (103) (both from Thermo Fisher Scientific) followed by heating at 85˚C for 10 min to denature and reduce all the proteins present in the samples.…”
Section: Protein Gels and Western Blotmentioning
confidence: 99%